Kuantifikasi Flavonoid dan Analisis Aktivitas Antioksidan Ekstrak Daun Nilam (Pogostemon cablin) Menggunakan Uji DPPH - Anggraini, Natasya Dila Putri; Pramukantoro, Ganet Eko; Novita, Mega; Marlina, Dian (Jurnal Teknik Kimia USU, 2025)
Patchouli leaves (Pogostemon cablin) are known to contain flavonoid compounds with potential antioxidant properties. However, comparative data on flavonoid content and antioxidant activity across different extract fractions of patchouli leaves remain limited. To address this gap, the present study was conducted to analyze the total flavonoid content and evaluate the antioxidant activity of the ethanol extract and three solvent fractions—n-hexane, ethyl acetate, and wáter using the DPPH method as an indicator of free radical scavenging activity. The extraction was carried out through maceration, followed by fractionation. The determination of flavonoid content employed a colorimetric method based on the aluminum chloride reaction, while antioxidant activity was assessed using the DPPH assay. The results revealed that the ethyl acetate fraction contained the highest flavonoid concentration (1.615 ± 0.0591%) and exhibited very strong antioxidant activity, with an IC₅₀ value of 17.3909 ± 0.1327 μg/mL. These findings suggest that the ethyl acetate fraction holds significant potential as a natural antioxidant agent, with possible applications in the pharmaceutical field or nutraceutical-based health products.